Morningness–eveningness and intrasexual competition in men. (April 2015) - Ponzi, Davide; Henry, Andrea; Kubicki, Konrad; Nickels, Nora; Wilson, M. Claire; Maestripieri, Dario
Highlights: We tested the hypothesis that evening types are more intrasexually competitive. We measured scores of the Intrasexual Competition Scale (ICS) in young college men. We used both OLS and robust regression. The regression models showed that eveningness predicted higher scores of ICS. The result was independent of personality traits. Abstract: A growing body of research points to a relationship between chronotype and socio-sexuality, especially in men, such that evening-types appear both to be more short-term mating oriented than morning-types and to possess more personality traits and other behavioral characteristics that facilitate sexual promiscuity. This study contributes to and expands this body of research by investigating the relationship between chronotype and intra-sexual competition. We tested the prediction that, in a subject population of young heterosexual men, evening-types would score higher on intra-sexual competition in the context of mating. The results were consistent with our prediction and showed that the association between chronotype and intra-sexual competitiveness is not the by-product of correlations with personality measures. Higher intra-sexual competitiveness in men who are evening-types may contribute to their higher short-term mating success reported by previous studies. Evolutionary hypotheses testing predictions derived from sexual selection or life history theory can make a significant contribution to our understanding of the functional significance of inter-individual variation in chronotype and its associated psychological and behavioral traits.